Virulence gene regulation by nucleoid associated proteins in Salmonella typhimurium : a role for Fis in Salmonella pathogenicity island 2 gene regulation - Carroll, Ronan (Trinity College (Dublin, Ireland). Department of Microbiology, 2004)
Nucleoid associated proteins are involved in many diverse biological functions in S. typhimurium. In addition to their structural role within the genome they have been im plicated in transcriptional regulation of a variety of genes, including those involved in virulence. In this study the role of nucleoid-associated proteins in S. typhimurium virulence gene regulation was investigated.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin